2020
DOI: 10.1111/1440-1681.13230
|View full text |Cite
|
Sign up to set email alerts
|

The long non‐coding RNA HCG18 promotes the growth and invasion of colorectal cancer cells through sponging miR‐1271 and upregulating MTDH/Wnt/β‐catenin

Abstract: Long non‐coding RNAs (lncRNAs) have recently emerged as key regulators of the occurrence and progression of various human cancers, including colorectal cancer. However, the regulatory mechanism of lncRNAs in the tumorigenesis of colorectal cancer remains poorly understood. In this study, we aimed to elucidate the potential role of lncRNA HCG18 in colorectal cancer. Herein, we found that HCG18 expression was significantly upregulated in colorectal cancer tissues and cell lines. Knockdown of HCG18 significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 44 publications
(116 reference statements)
2
35
0
1
Order By: Relevance
“…Knockdown of HCG18 inhibited the proliferation, migration, invasion, metastasis, while induced the apoptosis of cancer cells. [31][32][33]36,37 Also, silencing of HCG18 suppressed the growth of xenografts in mice. 36 Mechanistically, HCG18 was reported to competitively bind to miR-140, 31 miR-214-3p, 32 miR-1271, 33 miR-34a-5p 35 and miR-152-3p 34 to respectively enhance the expressions of the target genes of these miRNAs, including cyclin D1, CENPM, MTDH, HMMR and DNAJB12.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of HCG18 inhibited the proliferation, migration, invasion, metastasis, while induced the apoptosis of cancer cells. [31][32][33]36,37 Also, silencing of HCG18 suppressed the growth of xenografts in mice. 36 Mechanistically, HCG18 was reported to competitively bind to miR-140, 31 miR-214-3p, 32 miR-1271, 33 miR-34a-5p 35 and miR-152-3p 34 to respectively enhance the expressions of the target genes of these miRNAs, including cyclin D1, CENPM, MTDH, HMMR and DNAJB12.…”
Section: Discussionmentioning
confidence: 99%
“…XIST significantly increases its expression in both CRC tissue sample and CRC cells and promotes CRC cell proliferation by the miR-132-3p/MAPK1 axis [35]. HCG18 promotes the growth and invasion of CRC cell via miR-1271/MTDH/Wnt/βcatenin signaling [36]. High expression of HOXA11-AS is a risk factor for distant metastasis and poor clinical outcomes in numerous tumors [37].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2017) suggested that BET-Bromodomain inhibitor JQ1 synergized ABT-263 against CRC cells by inhibiting c-Myc-induced miR-1271 expression. HCG18 exerts a potential oncogenic function in CRC by enhancing MTDH/Wnt/ b-catenin signaling through sponging of miR-1271 (Li et al, 2020). Xie et al (2018) showed in pancreatic cancer (PC) that miR-1271 negatively regulated AKT/mTOR signaling and promoted apoptosis by targeting PDK1 in PC.…”
Section: Mir-1271 and Upstream Regulatorsmentioning
confidence: 99%